Conflict Management of School Administrators and the Motivation for the Performance of Teachers in Schools under Pattani Primary Educational Service Area Office 2 - Aryohsae, waekoleeyoh; Kao-ian , Jarunee; Suwanno , Phimpawee (Al-HIKMAH Journal, 2024)
The purpose of this research is to study Conflict Management of School Administrators and the Motivation for the Performance of Teachers in Schools, to compare conflict management of school administrators and Motivation for teachers Performance in Schools classified by gender, work experience and the size of the school, to study the relationship between conflict management of school administrators and the motivation for teachers Performance in school, to process the recommendations of conflict management of school administrators and the motivation for the Performance in schools, The samples used in this research were administrators and teachers under Pattani Primary Educational Service Area Office for 2,academic year 2022 for 336 people. The tools used in this research are 5 point rating scale questionnaire consisting of a questionnaire on conflict management of school administrators and a questionnaire on teachers’ motivation to work in schools. Statistics used in data analysis consisted of percentage, frequency, percentage, mean, and standard deviation. t-test, F-test, and Pearson’s correlation coefficient. The results show that First, Conflict management of school administrators and motivation for teachers performance in school the overall was at a high level., Comparison conflict management of school administrators and the motivation for teachers performance in school, classified by gender, work experience and the size of the school, the overall it is not different, The relationship between conflict management of school administrators and motivation for teachers performance in school, had a moderate Positive relationship in all aspects with statistical significance at the .01 level, Suggestions on conflict management of school administrators and teachers performance , namely administrators must express their intentions and clear stances. There must be a process for mediating conflicts that arise with justice.